2012
DOI: 10.3748/wjg.v18.i36.5034
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of neuropilin-1 and semaphorin 3A after partial hepatectomy in rats

Abstract: The interplay of Nrp-1 and Sema3A shown in our results may lead to a better understanding of interaction between sinusoidal remodeling and SECs during liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Our EC-specific results of NRP1 are in agreement with IHC previously reported 9,10 . NRP1 is typically found in arteries, not veins, during development 32 ; yet in the adult liver, NRP1 is expressed on arteries, veins, and capillaries 9 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our EC-specific results of NRP1 are in agreement with IHC previously reported 9,10 . NRP1 is typically found in arteries, not veins, during development 32 ; yet in the adult liver, NRP1 is expressed on arteries, veins, and capillaries 9 .…”
Section: Discussionsupporting
confidence: 92%
“…sNrp1 is expected to bind and sequester not only VEGF but also other Nrp1 ligands including PlGF, VEGF-B, and SEMA3A. PlGF, an angiogenic ligand, is upregulated after PHx 42 ; whereas SEMA3A, an anti-angiogenic ligand, is significantly downregulated during the first 6 days following PHx 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of axon guidance in liver regeneration may be mediated by secreted third class semaphorins (Sema3A-G), which bind to a membrane receptor complex whose main component is a transmembrane glycoprotein neuropillin 1 or neuropillin 2, or a heterodimer of the two ( 39 ). The interaction between the semaphorins 3A and neuropillin 1 is also notable in the angiogenic processes ( 40 ). The present study revealed increased expression of neuropillin 1 and neuropillin 2 in the group without application of stem cells between day 0 and 9.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, specimens obtained at the reoperation showed positive immunoreactivity. Similarly, NRP-1 is constitutively expressed in sinusoidal endothelial cells in normal liver, but its expression increases following resection of liver for sinusoidal remodeling (29). NRP-1 expression can be stimulated in response to tissue injury or hypoxic conditions (30,31).…”
Section: Discussionmentioning
confidence: 99%